1991
DOI: 10.1302/0301-620x.73b6.1955448
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral facet dislocations and fracture-dislocations of the cervical spine

Abstract: We treated 36 patients with unilateral facet dislocations or fracture-dislocations of the cervical spine at the Mayo Clinic between 1975 and 1986. Adequate records were available for 34: ten patients were treated by open reduction and posterior fusion, and 24 by nonoperative management. Of these, 19 had halo traction followed by halo-thoracic immobilisation, four had a simple cervicothoracic orthosis, and one received no active treatment. Anatomical reduction was achieved more frequently in the operative group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 0 publications
0
58
0
3
Order By: Relevance
“…In the operatively treated 10 patients (wiring by posterior approach and fusion), they reported that residual subluxations or angulations were not seen at late period and suffering from pain was less than nonoperatively treated group. 5 In the series by Lifeso et al, 4 none of the six patients treated by halo-vest and 12 patients treated with hard-collar had success. Buchoz and Cheung suggested that patients with unilateral facet fractures with perched facets should be surgically stabilized rather than a trial of halo-vest immobilization.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In the operatively treated 10 patients (wiring by posterior approach and fusion), they reported that residual subluxations or angulations were not seen at late period and suffering from pain was less than nonoperatively treated group. 5 In the series by Lifeso et al, 4 none of the six patients treated by halo-vest and 12 patients treated with hard-collar had success. Buchoz and Cheung suggested that patients with unilateral facet fractures with perched facets should be surgically stabilized rather than a trial of halo-vest immobilization.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4][5][6] Although oblique views are the best plain radiographic views to diagnose a lateral mass fracture, they are still not as sensitive as CT and the rotation of the neck is dangerous in cervical traumas. Another reason for the lack of sensitivity is the difficulty in imaging the cervical lower spine on lateral plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations